Using Virtual Laboratory: A Profile of Students' Self-Efficacy on Electrochemistry - Febrian Solikhin; Kristian Handoyo Sugiyarto; Jaslin Ikhsan (The University of Mataram, 2022)
This study aimed to analyze the profile of students' self-efficacy in the use of virtual laboratory in electrochemistry class. It is quantitative descriptive research. The total subject of this research was 90 students from grade 12th public senior high school. Three classes were selected randomly to determine the sample: C class using conventional laboratory, E-1 class using virtual laboratories as a substitute, and E-2 class using both a virtual laboratory as a supplement. The instrument was a self-efficacy questionnaire that consisted of 22 items. The data were analyzed and categorized into 5 rating categories: very high, high, fair, low, and very low. The results showed that the profile of students' self-efficacy in the E2-class was highest than in 2 other classes.